Global world: a problem of governance. Issue 2 (23rd June 2014) - Nikolayevich Chumakov, Alexander
Abstract : Purpose: – The purpose of this paper is to include the following items: to show the absolute necessity of managing the international community, to explore the fundamental possibility of managing the global world, to prove or disprove such a possibility, to determine the real background of global governance in modern conditions and to show the methods of transition toward global governance. Design/methodology/approach: – The main methodological principles used in writing the paper are: the principle of the integrity of the world; the understanding of globalization as an objective historical process; the principle of historical sequence of the considered event; the principle of priority of the general over the particular, as well as of the global over the regional and the local. Findings: – As a result of the proposed research, it is shown that the global world needs to be managed. Prerequisites for the management of the global world are identified, among which the most important are morality and rights. It is shown that for management of the global world there should not only be global government, but also other branches of government, such as a World Parliament and a judicial system based on global law. Research limitations/implications: – A clear distinction between the management and regulation of social relations is made. The need to further explore the concepts of international law and global right is stated. Practical implications: – National sovereignty increasingly must give place to global governance structures. Social implications: – The need to build a global civil society is evident. Originality/value: – The absolute necessity and possibility of regulating the world community are shown. New approaches to solving this problem are proposed. They are based on existing assumptions in the field of executive and legislative power and also involve the creation of new structures, primarily in the area of the judiciary.